Impact of a national enhanced recovery after surgery programme on patient outcomes of primary total knee replacement: an interrupted time series analysis from "The National Joint Registry of England, Wales, Northern Ireland and the Isle of Man". Issue 9 (September 2019) - Garriga, C.; Murphy, J.; Leal, J.; Price, A.; Prieto-Alhambra, D.; Carr, A.; Arden, N.K.; Rangan, A.; Cooper, C.; Peat, G.; Fitzpatrick, R.; Barker, K.; et al.
Summary: Objective: We aimed to test whether a national Enhanced Recovery After Surgery (ERAS) Programme in total knee replacement (TKR) had an impact on patient outcomes. Design: Natural-experiment (April 2008–December 2016). Interrupted time-series regression assessed impact on trends before-during-after ERAS implementation. Setting: Primary operations from the UK National Joint Registry (NJR) were linked with Hospital Episode Statistics (HES) data which contains inpatient episodes undertaken in National Health Service (NHS) trusts in England, and Patient Reported Outcome Measures (PROMs). Participants: Patients undergoing primary planned TKR aged ≥18 years. Intervention: ERAS implementation (April 2009–March 2011). Outcomes: Regression coefficients of monthly means of Length of stay (LOS), bed day costs, change in Oxford knee scores (OKS) 6-months after surgery, complications (at 6 months), and rates of revision surgeries (at 5 years). Results: 486, 579 primary TKRs were identified. Overall LOS and bed-day costs decreased from 5.8 days to 3.7 and from £7607 to £5276, from April 2008 to December 2016. Oxford knee score (OKS) change improved from 15.1 points in April 2008 to 17.1 points in December 2016. Complications decreased from 4.1 % in April 2008 to 1.7 % in March 2016. 5-year revision rates remained stable at 4.8 per 1000 implants years in April 2008 and December 2011. After ERAS, declining trends in LOS and bed costs slowed down; OKS improved, complications remained stable, and revisions slightly increased. Conclusions: Different secular trends in outcomes for patients having TKR have been observed over the last decade. Although patient outcomes are better than a decade ago ERAS did not improve them at national level.